The effectiveness of advertising campaign to overcome animal abuse issue in Malaysia / Aznul Muzahfar Abu Shahid - Abu Shahid, Aznul Muzahfar (Faculty of Art and Design, 2013)
This academic writing is about analyzing issues and problems that arises and finding a way to overcome the problem. Animal abuse is a crime that is getting serious day by day. With this academic writing, student can study the issue and to find a solution to overcome this problem. In chapter one, this chapter will be discussing about the background of the research. This is where the academic writing will show the details of the background of the study. It includes background study, problem statement, related research and literature review and significant of the study. In chapter two, this chapter will show the significance of study, which is to give benefits to the animals, to the public and also to the country. This second chapter will be discussing the objectives in fighting animal abuse. Hence, This chapter also related with giving the detail of explanation and the method of gathering and recording the information. The method of collecting the research can be divided into two, which are primary data and secondary data.